Hypercompact stellar clusters: morphological renditions and spectrophotometric models. Issue 2 (6th May 2020) - Lena, D; Jonker, P G; Rauer, J P; Hernandez, S; Kostrzewa-Rutkowska, Z
ABSTRACT: Numerical relativity predicts that the coalescence of a black hole (BH) binary causes the newly formed BH to recoil, and evidence for such recoils has been found in the gravitational waves observed during the merger of stellar-mass BHs. Recoiling (super)massive BHs are expected to reside in hypercompact stellar clusters (HCSCs). Simulations of galaxy assembly predict that hundreds of HCSCs should be present in the halo of a Milky Way (MW)-type galaxy, and a fraction of those around the MW should have magnitudes within the sensitivity limit of existing surveys. However, recoiling BHs and their HCSCs are still waiting to be securely identified. With the goal of enabling searches through recent and forthcoming data bases, we improve over existing literature to produce realistic renditions of HCSCs bound to BHs with a mass of 10 5 M⊙ . Including the effects of a population of blue stragglers, we simulate their appearance in Pan-STARRS and in forthcoming Euclid images. We also derive broad-band spectra and the corresponding multiwavelength colours, finding that the great majority of the simulated HCSCs fall on the colour–colour loci defined by stars and galaxies, with their spectra resembling those of giant K-type stars. We discuss the clusters properties, search strategies, and possible interlopers.